Usefulness Differs Between the Visual Assessment and Specific Binding Ratio of 123I-Ioflupane SPECT in Assessing Clinical Symptoms of Drug-Naïve Parkinson’s Disease Patients - Murakami, Hidetomo; Kimura, Atsushi; Yasumoto, Taro; Miki, Ayako; Yamamoto, Ken; Ito, Naohito; Momma, Yutaro; Owan, Yoshiyuki; Yano, Satoshi; Ono, Kenjiro (Frontiers in Aging Neuroscience, 2018)
Background: In clinical practice, assessment of the striatal accumulation in 123I-ioflupane single photon emission computed tomography (SPECT) is commonly performed calculating the Specific Binding Ratio (SBR) for the whole striatum. On the other hand, visual assessment of striatal accumulation in the SPECT was recently established. However correlations of visual assessment with motor and cognitive functions in Parkinson’s disease (PD) have rarely been examined. Differences in the usefulness of these assessments at clinics are uncertain. Objective: We performed this study to compare correlations of cognitive and motor functions in drug-naive PD between the SBR and visual assessment using 123I-ioflupane SPECT. Methods: Cognitive and motor assessments and 123I-ioflupane SPECT were performed in 47 drug-naïve PD patients with Mini-mental State Examination scores of ≥25. Cognitive function was assessed using the total score and 6 subscores of the Montreal Cognitive Assessment (MoCA) and 10 separate subtests of the Neurobehavioral Cognitive Status Examination (COGNISTAT). Motor function was assessed using the Hoehn and Yahr scale and Unified Parkinson’s Disease Rating Scale (UPDRS). Accumulation of 123I-ioflupane was determined by visual assessment based on 5 grades: 1, burst striatum; 2, egg-shaped; 3, mixed type; 4, eagle wing; 5, normal striatum; and by calculating SBR averaged for the bilateral striatum using the DaTView computer software commonly used in clinical practice. Each SPECT assessment was compared with each subscore for cognitive and motor assessments. Results: Spearman correlation analysis showed SBR was significantly correlated with the MoCA subscores of visuospatial function and attention, and with COGNISTAT subtests of attention. Visual assessment showed significant negative correlation with the Hoehn and Yahr scale. Mean score of postural instability in patients with visual grade of 1 was significantly higher than those in patients with visual grades of 2 and 3. Conclusion: Clinical symptoms reflected by 123I-ioflupane SPECT differ between the SBR and visual assessment. SBR reflects some cognitive functions, whereas a visual assessment grade of 1, which signifies decreased uptake of 123I-Ioflupane in the caudate nucleus, reflects postural instability. Thus, the caudate nucleus may play an important role in posture maintenance. Our results suggest that performing both assessments is of value.